Relationship between Insulin Levels and Nonpsychotic Dementia: A Systematic Review and Meta-Analysis - Qiu-xia Pan; Xiao-juan Li; Yue-yun Liu; Fang-fang Wang; Ya-jing Hou; Qing-lai Bian; Wen-qi Qiu; Zhi-yi Yan; You-ming Jiang; Jia-xu Chen (Neural Plasticity)
Objectives. To explore the relationship between insulin levels and nonpsychotic dementia. Methods. Six electronic databases (PubMed, Cochrane, SCI, CNKI, VIP, and Wanfang) were searched from January 1, 2007, to March 1, 2017. Experimental or observational studies that enrolled people with nonpsychotic dementia or abnormal insulin levels in which insulin levels or MMSE scores (events in nonpsychotic dementia) were the outcome measures. Random-effects models were chosen for this meta-analysis. Sample size, mean, s.d., and events were primarily used to generate effect sizes (with the PRIMA registration number CRD42017069860). Results. 50 articles met the final inclusion criteria. Insulin levels in cerebrospinal fluid were lower (Hedges’ g = 1.196, 95% CI = 0.238 to 2.514, and P=0.014), while the levels in peripheral blood were higher in nonpsychotic dementia patients (Hedges’ g = 0.853 and 95% CI = 0.579 to 1.127), and MMSE scores were significantly lower in the high insulin group than in the healthy control group (Hedges’ g = 0.334, 95% CI = 0.249 to 0.419, and P=0.000). Conclusions. Our comprehensive results indicate that blood insulin levels may increase in patients with nonpsychotic dementia.